Vegetable Waste Biodrying Treatment for Energy Recovery as Refuse Derived Fuel Potential - Iva Yenis Septiariva; I Wayan Koko Suryawan; Mega Mutiara Sari (Politeknik Negeri Malang, 2022)
Vegetable waste is a type of biodegradable organic waste found in every location in Indonesia. In addition, vegetable waste also dominates food waste. One of the ways to use vegetable waste is to use energy recovery. Energy recovery of vegetable waste can be done by time-dependent biodrying and bioactivator. This study aimed to determine the effect of time and activator application on the vegetable waste biodrying process. In this study, 0.5 kg of waste is used with an airflow rate of 15 liters/minute, the temperature in the process is in the range of 28.4-34.1°C. The bioactivators used in this study were baker's yeast, tempeh, and tape. The maximum decrease in mass occurs in the biodrying process with the addition of a bioactivator. The multivariate effect test results showed an effect of time and bioactivator on changes in water content and caloric value. However, the interaction between time and bioactivator only affects the water content. This is because the degradation process occurs utilizing microorganisms stored in the bioactivator liquid and water in vegetable waste. Further research is needed to know the effect of other variables in the biodrying process, especially the right detention time and bioactivators that accelerate the rate of degradation.